Sports-related concussion assessment in professional racing and freestyle bicycle motocross (BMX): A scoping review and call to action - Leonard-Hawkhead, B.; McCaffrey, D.; Heron, N. (Journal of Science and Cycling, 2023)
Bicycle Motocross (BMX), both Racing and Freesyle, have gained popularity since the 1960s, evidenced by their debutes within the 2008 and 2020 Olympics, respectively. Sports-related concussions (SRCs) are ubiquitous within cycling, particularly in the discipline of BMX. The management of concussion in sport is an important issue, and many international sporting bodies have published guidelines. In this review, literature is searched systematically in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA): Extension for Scoping Reviews for sports-related concussion assessment in Bicycle Motocross. Only two items were included within the review and shows the distinct lack of discipline specific, SRC assessment guidance and recommends further research to help apply the Sport Concussion Assessment Tool version 6 to BMX.